Efeito do tratamento combinado da fotobiomodulação e ultrassom terapêutico em indivíduos acometidos com fibrose pulmonar - Garcia, Vanessa (Universidade Federal de São Carlos, 2026)
Pulmonary fibrosis is a chronic, progressive and irreversible interstitial lung disease, characterized by inflammation and thickening of the alveolar walls, which compromise gas exchange and cause hypoxia. Its etiology is unknown, but genetic factors and environmental factors are associated. Symptoms vary between patients, with the following being common: dyspnea on exertion, dry cough, hypoxemia and without treatment, the average survival is 3 to 5 years. The objective of this pilot study was to evaluate the effects of therapeutic treatment with photobiomodulation associated with therapeutic ultrasound, performed on the palms of the hands, associated with respiratory exercises in patients with pulmonary fibrosis. Twelve patients were included, divided into a Placebo group – n=5 (respiratory physiotherapy) and a Treated group – n=7 (respiratory physiotherapy + Recupero®). The Recupero® equipment, developed by the São Carlos Institute of Physics (USP), was used with the following parameters: for the laser, red and infrared light were used, respectively, with wavelengths of 660 nm and 808 nm simultaneously, and the ultrasound parameters were pulsed mode, frequency of 1 mHz, intensity of 0.8 W/cm2, 48 Hz pulse applied to the palms of the hands for 10 minutes each, totaling a laser application time of 20 minutes. The protocol was performed twice a week for five weeks, with 50-minute sessions and continuous monitoring of vital signs. Both groups performed the exercise protocol, which included diaphragmatic exercises, pursed-lip exercises, exercises with a stick, and exercises with a Volumetric Respiron (both, 2 sets of 10 repetitions); and minicycle exercises for the upper and lower limbs (both, increasing the time by 1 minute every 2 sessions, finishing 10 sessions with a time of 5 minutes, including pedaling). The following assessment and reassessment mechanisms were used: Anamnesis form (personal data, Spirometry, Maximum Inspiratory Pressure; Maximum Expiratory Pressure; Peak Flow; Sit-to-Stand Test; Timed Up and Go; 6-Minute Walk Test and Visual Analogue Scale), questionnaires (King’s Brief Interstitial Lung Disease Questionnaire; London Chest Activity of Daily Living Scale; Pittsburgh Sleep Quality Index and Quality of Life Short Form 36). The results were analyzed at baseline, at the end of the study, and after 60 days, and demonstrated that respiratory exercises combined with photobiomodulation and ultrasound enhanced clinical gains, with the Treated group outperforming the Placebo group in almost all parameters. After 60 days, the values remained above the initial levels, confirming the potential of these technologies in respiratory physiotherapy for patients with pulmonary fibrosis. We conclude that the results indicate that the combination of respiratory exercises and the synergy of photobiomodulation and therapeutic ultrasound constitutes a more efficient rehabilitation option, pointing to a new direction for the treatment of pulmonary fibrosis and promoting improved quality of life.
Effect of combined laser and ultrasound treatment in individuals with pulmonary fibrosis
Keywords: Fibrose pulmonar; Fotobiomodulação; Ultrassom terapêutico; Exercícios respiratórios; Pulmonary fibrosis; Photobiomodulation; Therapeutic ultrasound; Respiratory exercises; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; 3. Saúde e Bem-Estar